If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 = 3x + -2 Reorder the terms: 37 = -2 + 3x Solving 37 = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 37 + -3x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 37 + -3x = -2 + 0 37 + -3x = -2 Add '-37' to each side of the equation. 37 + -37 + -3x = -2 + -37 Combine like terms: 37 + -37 = 0 0 + -3x = -2 + -37 -3x = -2 + -37 Combine like terms: -2 + -37 = -39 -3x = -39 Divide each side by '-3'. x = 13 Simplifying x = 13
| 15+3t-5-8t= | | 200=100x | | 8x-28=2(4x-14) | | 3/4×1/9 | | 3x+18=20-2x | | y=4x^2-5x-6 | | 200/10 | | -6k+6-3k+8= | | 3x-y=31 | | 5.7n+4.1=2.96 | | Y^2-9=11x | | (15)29-n=225 | | 15(29-n)=225 | | 15(n-29)=225 | | s=1/8(80) | | s+1/8=80 | | 80s=1/8 | | 61/2x33/13 | | 102+x=(4x+6) | | 2s+4=5(-4-2s) | | (x^2-3x+2)(x^2+3x-8)=24 | | 3+3*6-2=0 | | 3-2(b-2)=2-7b | | 12h=4(2h-5) | | 5x+8y-9x= | | x^3-x^2-11x=0 | | 4(-6)-5(2)/2(2) | | x+x(0.13)=7091.88 | | Y-4X-1=6X+6X^2 | | 6t+4=3t-2 | | -t=9(t-10) | | 2x^2+2=-13 |